Prevailing leadership styles among the heads of student clubs at the Imam Abdulrahman Bin Faisal University as per Goleman emotional leadership Model - Alsmoul, Essa Mohammad Ali (Journal of Educational and Psychological Sciences, 2019)
This study aimed at identifying the prevailing leadership styles among the heads of students' clubs as per Goleman Emotional Leadership Model from the perspective of the members of the clubs and as related to their college, year and club category variables. To achieve the purpose of the study, the study employed the descriptive approach including a 43-survey questionnaire for the 6 domains of the leadership. SPSS was used in data analysis and in verifying the survey reliability and validity. The results of the study indicated that the visionary style was the most prevailing among heads of students' clubs with a mean of (4.77) followed by the coaching style (4.68), the democratic style (4.67) with high degrees and the commanding style (4.44) with mid degree; the coercive style of leadership was at the bottom of the leadership styles (3.13). The study also indicated that there were statistically significant differences that could be attributed to the science majors for students in their second year who are in majored clubs (clubs of academic majors). The study offered a package of recommendations related to its findings. Including the development of leadership skills of the heads of public clubs, because of the different faculties of the members of student clubs; to make the work environment club attractive environment for new members.
Keywords: leadership style; Daniel Goleman; emotional intelligence; heads of student clubs; Imam Abdul Rahman bin Faisal University